Crashes, Bailouts, Regulations - World Bank (Washington, DC, 2012)
With the recent stock market frauds in markets around the world such as the Madoff case in the U.S. and the recent Satyam fraud in India, no nation can hold its head high and claim to have good corporate governance. The reality is that the problems of fraud, faulty audits, misleading accounts, lack of transparency, conflicts of interest, criminal destruction of records and a long list of other corporate governance violations, are not limited to emerging markets but are very much in evidence in developed markets as well. Given recent events then, the importance of sound corporate governance is becoming increasingly apparent. International organizations like the Organization for Economic Co-operation and Development (OECD), the World Bank and the International Corporate Governance Network (ICGN), along with major fund managers, are formulating sets of codes and principles that can be applied globally. It is also clear, however, that governments have generally done a poor job of policing the complex world of finance and that the greater part of the task will be left to self policing on the part of the participants. There is no doubt about it: sound corporate governance pays. Several studies undertaken by various organizations have shown that: there is a direct relationship between good corporate governance and investment returns. The oversight that comes from transparency and accountability creates a structure where the managers are discouraged from mismanaging the company, be it though a lack of diligence or care, improper decision-making, or even intentioned unconscionable behavior.